The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.26417/ejis.v4i1.p100-107
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte Complexes Based on Chitosan and Natural Polymers

Abstract: For many years chitosan has been the subject of interest for its use in different medical fields due to its appealing properties such as biocompatibility, biodegradability, low toxicity and relatively low production cost from abundant natural sources. Chitosan is positively charged at low pH values, so it is spontaneously associated with negatively charged polyions in solution to form polyelectrolyte complexes. These chitosan based polyelectrolyte complexes exhibit favourable physicochemical properties with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Recently, the utility of carrageenans in drug delivery systems has been demonstrated, whereby carrageenans were used as gellingor viscosity-enhancing agents for controlled drug release systems with applications in tissue regeneration using therapeutic biomacromolecules (Guan, Li, & Mao, 2017;Li et al, 2014). Chitosan-carrageenan polyelectrolyte complexes are available, which can be used as excipients for various dosage forms (Mustafa, Tomescu, Mustafa, Cherim, & Sîrbu, 2016).…”
Section: Carrageenan: Structure and Biological Activitiesmentioning
confidence: 99%
“…Recently, the utility of carrageenans in drug delivery systems has been demonstrated, whereby carrageenans were used as gellingor viscosity-enhancing agents for controlled drug release systems with applications in tissue regeneration using therapeutic biomacromolecules (Guan, Li, & Mao, 2017;Li et al, 2014). Chitosan-carrageenan polyelectrolyte complexes are available, which can be used as excipients for various dosage forms (Mustafa, Tomescu, Mustafa, Cherim, & Sîrbu, 2016).…”
Section: Carrageenan: Structure and Biological Activitiesmentioning
confidence: 99%
“…The understanding and control of the degradation rate of chitin and chitosan-based devices is of great interest since degradation is essential in many small and large molecule releaseapplications and in functional tissue regeneration applications. Ideally, the rate of scaffold degradation should mirror the rate of new tissue formation or be adequate for the controlled release of bioactive molecules (Mustafa A., 2016). Thus, it is important to understand and control both the mechanism and the rate by which each material is degraded.…”
Section: Biological Properties Of Chitosan Biodegradabilitymentioning
confidence: 99%
“…In the 1970s it has been demonstrated that CHOS have anti-tumor effects, and reduce metastasis from tumors (Mustafa A., 2016). Initially it was believed that the antitumor activity was due to the cationic properties of CHOS, and later, the MW was discovered to play a major role.…”
Section: Tumor Growth Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, being a polysaccharide, chitosan needs to be cross-linked with a plethora of different molecules [ 15 , 16 , 17 , 18 ] to allow dimensional stability to be achieved in an aqueous environment, which is fundamental in the reusing process of the solid biocatalyst. Among them alginate, a linear unbranched polymer containing β-(1→4)-linked D-mannuronic acid and α-(1→4)-linked L-guluronic acid [ 19 ], is one of the most used [ 20 , 21 ]. Anyway, even when cross-linked, natural polymers can be prone to swelling and degradation, especially under harsh operating conditions, which may lead to the loss of enzyme activity and reduced lifespan of the immobilized enzymes.…”
Section: Introductionmentioning
confidence: 99%